Strengthening the links between planning and health in England. (16th April 2020) - McKinnon, Gemma; Pineo, Helen; Chang, Michael; Taylor-Green, Laura; Strategy, Annalise Johns; Toms, Rachel
Abstract : Gemma McKinnon and colleagues argue that multidisciplinary action in planning and health will contribute to more equitable communities and improved health and wellbeing